Preparation, characterization and electrical properties of fluorine-doped tin dioxide nanocrystals - Wu, Shanshan; Yuan, Shuai; Shi, Liyi; Zhao, Yin; Fang, Jianhui (Journal of colloid and interface science, 2010)
The HRTEM image and FFT pattern reveal that the fluorine doped SnO 2 nanocrystals are of cassiterite structure. Fluorine-doped tin dioxide (FTO) nanocrystals were prepared with a sol–gel process followed by a hydrothermal treatment using SnCl 4 and NH 4F as SnO 2 and fluorine dopant, respectively. The nanostructure and composition were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM), zeta potential analysis, electrochemical measurement technology and X-ray photoelectron spectroscopy (XPS) respectively. The diameter of the fluorine doped SnO 2 nanocrystal in rutile-type structure is about 10 nm. Compared to the pure SnO 2 nanocrystals, the fluorine doped SnO 2 nanocrystals can be dispersed homogeneously in H 2O, forming transparent sol with high stability. The powder of fluorine doped SnO 2 nanocrystals could be obtained by removing the solvent, and the electrical resistivity properties were measured by a four-point probe measurement. The results show that sheet resistances (Rs) of fluorine doped SnO 2 decrease with the increasing NH 4F/Sn molar ratio in the range from 0 to 2. However, further increase of NH 4F/Sn molar ratio from 2 to 5 leads to higher sheet resistance. The F/Sn molar ratio of fluorine doped SnO 2 measured by XPS is about 0.18 when NH 4F/Sn molar ratio is equal to 2, and the sheet resistance of fluorine doped SnO 2 powder is 110Ω/□.